2018
DOI: 10.18203/2319-2003.ijbcp20180646
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern and physician adherence to treatment guidelines in inpatients with urinary tract infection

Abstract: Background: Mainstay of management in urinary tract infection (UTI) is antibiotics and it is seen in recent years that antibiotic resistance is increasing. However, very few treatment guidelines exist for UTI and often treating physicians may not adhere to these guidelines. Aims: Current study was undertaken to analyze antimicrobial prescription pattern and utilization, and check for physician adherence to treatment guidelines in UTI.Methods: This retrospective, record-based study was carried out in a tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Study result showed that UTIs was more common in female which is consistent with two other studies perfomed on patients suffering from UTI (Ahmed, JAKRIBETTU, KOYAKUTTY, Arya, & Shakir, 2012; Gidamudi et al, 2015).Most Commonly prescribed drugs for treatment of UTI were antibiotics such as fluoroquinolones and cephalosporins this findings is accordance with other similar studies (Gidamudi et al, 2015;Sharma & Oommen, 2018). As the results of the study Pargavi B. et al,19% study also shows E. coli was the most commonly isolated organism in urine culture.…”
Section: Discussionsupporting
confidence: 90%
“…Study result showed that UTIs was more common in female which is consistent with two other studies perfomed on patients suffering from UTI (Ahmed, JAKRIBETTU, KOYAKUTTY, Arya, & Shakir, 2012; Gidamudi et al, 2015).Most Commonly prescribed drugs for treatment of UTI were antibiotics such as fluoroquinolones and cephalosporins this findings is accordance with other similar studies (Gidamudi et al, 2015;Sharma & Oommen, 2018). As the results of the study Pargavi B. et al,19% study also shows E. coli was the most commonly isolated organism in urine culture.…”
Section: Discussionsupporting
confidence: 90%
“…37 However a recent retrospective, record-based study recorded a contradictory finding with 98.1% drugs prescribed in generic form in a tertiary care hospital in inpatients with urinary tract infection. 38 Prescribing by generic name needs to be promoted in our hospital to curb drug duplication, medication error and adverse effects due to medication therapy. Almost two-third of patients showed good adherence with the prescribed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gidamudi et al and Sharma et al 2018. 7,8 Over the years procurement of Access group antibiotics declined by 20% and there was an increase watch group consumption. WHO goal is to target that 60% of all antibiotic's procurement should be from access group,9 but unfortunately in our study, that trend is going in opposite direction.…”
Section: Discussionmentioning
confidence: 99%